Pengembangan Sistem Reservasi Dokter Gigi berbasis Web dengan Integrasi API Telegram Bot - Ilham Bagas Harapan; Buce Trias Hanggara; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Dental and oral disease is one of the most common diseases in Indonesia. The results of the 2001 SKRT-Surkesnas morbidity study showed that dental disease was in the highest position out of the ten most common disease groups that people complained about. Doctor Prima Luthfia is a dentist who opens an independent dentist practice. A patient can have a consultation at Luthfia's doctor's practice by making an appointment with a doctor. Doctors cannot serve more than one because the practice is independent. Problems arise when Luthfia's doctor has two patients who have appointments at the same time due to Luthfia's scheduling error. From these problems, a solution is proposed which forms the basis of this research, where web-based development is carried out using the Telegram bot API integration. The method used is the waterfall, where in this method there are stages of literature study, needs analysis, system design, implementation, testing and evaluation. Using Node.js as a system development framework, Express.js as an API framework, and MongoDB as a database, the system development has been successfully carried out, and has been tested using the Blackbox method which results in 100% validation of system functions and Usability testing using the System Usability Scale with a score of 85.25 which reached the Acceptability Range criteria and obtained a B value in the Excellence category.